2018
DOI: 10.1088/1361-665x/aaafeb
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on static component generation from the primary Lamb waves propagating in a plate with nonlinearity

Abstract: Under the discipline of nonlinear ultrasonics, in addition to second harmonic generation, static component generation is another frequently used nonlinear ultrasonic behavior in non-destructive testing (NDT) and structural health monitoring (SHM) communities. However, most previous studies on static component generation are mainly based on using longitudinal waves. It is desirable to extend static component generation from primary longitudinal waves to primary Lamb waves. In this paper, static component genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 46 publications
3
17
0
Order By: Relevance
“…In fact, the stronger zero-frequency mode compared with the second harmonic was also obtained in [ 45 ] through a COMSOL simulation; nevertheless, it was ignored. The results of our simulation are consistent with those of a previous study [ 39 ]. Physically, the zero-frequency displacement mode represents the irreversible shift of a particle from its original equilibrium position.…”
Section: Simulationsupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, the stronger zero-frequency mode compared with the second harmonic was also obtained in [ 45 ] through a COMSOL simulation; nevertheless, it was ignored. The results of our simulation are consistent with those of a previous study [ 39 ]. Physically, the zero-frequency displacement mode represents the irreversible shift of a particle from its original equilibrium position.…”
Section: Simulationsupporting
confidence: 92%
“…To overcome these limitations, Sun et al (theory) [ 38 ] and Wan et al (simulation) [ 39 ] have shown that the signal of the zero-frequency mode is stronger than that of the traditional nonlinear harmonics for Lamb waves. Unlike the second harmonic, phase-velocity matching is not required for the zero-frequency mode accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies associated with nonlinear analysis methods have been reported in different works [64,65]. Similarly, methodological limitations caused by the propagation of linear excitation signals were described in Reference [66].…”
Section: Limitationsmentioning
confidence: 99%
“…In contrast to the traditionalpoint‐by‐point ultrasonicC‐scanning, the use of Lamb waves simplifies evaluation of microdamages in bigger structures as they can propagate longer distances with low decay rate and cover entire cross section . The low‐frequency S 0 − S 0 mode pair andhigh‐frequency S 1 − S 2 or S 2 − S 4 resonant mode pairs can be used to fulfill the requirements for cumulative propagation of the second harmonic …”
Section: Introductionmentioning
confidence: 99%
“…2 The low-frequency S 0 − S 0 mode pair andhigh-frequency S 1 − S 2 or S 2 − S 4 resonant mode pairs can be used to fulfill the requirements for cumulative propagation of the second harmonic. 11,13,14 The ultrasonic nonlinearity parameter estimated for a material using amplitude of second harmonic contains information about the nonlinearity of the propagating medium. 15 In the case of longitudinal waves, the material nonlinearity can be estimated using the equation 2,16 β ¼ 8…”
mentioning
confidence: 99%